2008
DOI: 10.1108/02637470810894885
|View full text |Cite
|
Sign up to set email alerts
|

Performance measurement in facilities management: driving innovation?

Abstract: Purpose -This paper aims to examine the state of knowledge of performance measurement in facilities management, in particular regarding the concepts underlying benchmarking in relation to its ability to drive innovation in the industry. Design/methodology/approach -An evaluation of the key issues surrounding performance measurement and the effective application of benchmarking systems are examined, exploring the possibility of applying a benchmarking technique to measure facilities performance. Findings -The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 35 publications
(39 reference statements)
1
85
0
Order By: Relevance
“…The aim is to present Norwegian knowledge development as experienced by the authors and found in the literature. FM has developed as a field since 1978 (Pitt and Tucker, 2008), and has, since that early beginning, focused on issues related to productivity. It is likely that the development of FM was influenced by society's craving for increasing efficiency following the economic crisis of midst 1970s and the evolvement of new public management (NPM) (Klungseth, 2015).…”
Section: Scope and Purposementioning
confidence: 99%
“…The aim is to present Norwegian knowledge development as experienced by the authors and found in the literature. FM has developed as a field since 1978 (Pitt and Tucker, 2008), and has, since that early beginning, focused on issues related to productivity. It is likely that the development of FM was influenced by society's craving for increasing efficiency following the economic crisis of midst 1970s and the evolvement of new public management (NPM) (Klungseth, 2015).…”
Section: Scope and Purposementioning
confidence: 99%
“…According to BIFM [14], FM "encompasses multi-disciplinary activities within the built environment and the management of their impact upon people and the workplace." Pitt and Tucker [16] suggest that the purpose of FM is integrating noncore services to adequately support the core functions and objectives of an organization. To achieve this function, Kincaid [17] observes effective FM need to recognize three key characteristics:…”
Section: The Strategic Role Of Facilities Managementmentioning
confidence: 99%
“…Amaratunga & Baldry [49] contend that, measurement is not an end in itself, but a tool for more effective management. It is argued that organizations need to transition from just measuring performance to actually managing it in order to maximize the use of its performance measurement outcomes and create strategic value [16,49]. To successfully transition from performance measurement to performance management Amaratunga & Baldry [49] suggests that the right organizational structure for performance measurement, and the ability to use performance measurements outcomes to effect change in the organization must be in place.…”
Section: 3mentioning
confidence: 99%
“…After the 90"s other definitions came out and according to Pitt and Tucker (2008), organizational performance is defined as a vital sign of the organization, showing how well activities within a process or the outputs of a process achieve a specific goal. Boxall and Steeneveld (1999) on the other hand argued that there is no need to prove the relationship between firm critical influence on performance and labor management as it is self-evident that the quality of human resource management is a critical influence on the performance of the firm.…”
Section: R M B Rmentioning
confidence: 99%